The Role of Social Support in Career Decision-Making through Career Adaptability - Hana, Zumrotul; Sugiharto, DYP; Sutoyo, Anwar (Jurnal Bimbingan Konseling, 2022)
Ideal career decision-making is when a person realizes the need and has the readiness and capability to make decisions correctly. However, career decision-making may become an obstacle that hinders student development if not handled properly. This research was conducted to explore the role of career adaptability in mediating between social support and career decision-making. This study belongs to the ex-post facto type, which used the correlational research design. The respondents included 286 students from 5 private MA (Madrasah Aliyah, equal to high school). The findings proved that: 1) Social support affects career decision-making, 2) Social support on career adaptability, 3) Social support on career decision-making through career adaptability, and 4) career adaptability on career decision-making. The results of the study showed how career adaptability could mediate between social support and career selection.